ظاهرة التواتر الأسلوبي في رواية "حكاية بحار"لحنا مينة /The phenomenon of stylistic frequencies in the novel "The Tale of a Sailor" by Hanna Mina - Iftikhar Mohieddin (مجلة الدراسات اللغوية والأدبية (Journal of Linguistic and Literary Studies), 2023)
ملخص البحث: يهدف هذا البحث إلى دراسة ظاهرة التواتر الأسلوبي في رواية حكاية بحار، للكاتب العربي حنا مينة دراسة تحليلية بنيوية نقدية هادفة ؛وذلك للوقوف على الفلسفة العامة للتكرار التواتري لبعض التقنيات السرديةالتي يوظفها الكاتب في عملية نسج نص الرواية، وأثر ذلك في العملية التعبيرية ، لذلك فقد تبنت الباحثة المنهج التحليلي الوصفي في تتبع التواترات الموجودة في داخل النص الروائي بوصفها ظاهرة أسلوبية بنيوية ، وهذه التواترات متنوعة، منها الخاص بالجانب الأسلوبي اللغوي-إن صح التعبير- ومنها الخاص بالجوانب التصويرية البلاغية داخل النص من جهة أخرى، يضاف إلى ذلك تركيز الباحثة على التقنيات السردية البنائية الأخرى التي وظفها الكاتب وبرع فيها، مما دفع إلى إنتاج هذا النص الروائي المتميز. وبعد قراءة الرواية وتحليلها تحليلاً دقيقاً، وجدت الباحثة أن الكاتب كان قد وظف سلسلة من التواترات الأسلوبية التي شكلت تقنيات بنائية تعبيرية؛ كان لها الأثر الملحوظ في تشكيل النص الروائي بأبعاده كافة. الكلمات المفتاحية: التواتر، الأسلوب،تقنيات السرد،البنيوية، حكاية بحار. Abstract This research aims at studying the phenomenon of stylistic continuity in the novel "The Tale of a Sailor" by the Arab writer Hanna Mina, an analytical, structural, and critical study aimed at identifying the general philosophy of the cyclical repetition of some narrative techniques employed by the writer in the process of construction the novel, and its impact on the expressive process. The novelty in this study is that it deals with the frequencies within the fictional text as a structural stylistic phenomenon on the one hand, and that these frequencies are diverse, including those related to the stylistic-linguistic aspect - if the expression is right - and those pertaining to the pictorial and rhetorical aspects within the text on the other hand, in addition to that The researcher focused on other constructive narrative techniques that the writer employed and excelled in, which prompted the production of this distinguished fictional text. After reading and analyzing the novel carefully, the researcher found that the writer had employed a series of stylistic frequencies that formed expressive constructive techniques. It had a remarkable impact in construction the narration text in all its dimensions. Keywords: frequency, style, narration techniques, structuralism, sailor’s tale. Abstrak Penyelidikan ini bertujuan untuk mengkaji fenomena kekerapan gaya dalam novel A Sailor’s Tale, oleh penulis Arab Hanna Mina. Kajian menggunakan kaedah analisa, struktur, dan kritis. Ini adalah untuk menentukan falsafah umum pengulangan yang kerap bagi beberapa teknik naratif yang digunakan oleh penulis dalam proses menganyam teks novel, dan kesannya terhadap proses penceritaan. Oleh itu, pengkaji menggunakan pendekatan analitik deskriptif dalam menjejaki frekuensi yang terdapat dalam teks naratif sebagai fenomena stilistik struktur. Frekuensi ini adalah pelbagai, antaranya ada yang berkaitan dengan aspek stilistik linguistik dan ada yang berkaitan. kepada aspek bergambar dan retorik dalam teks sebaliknya, sebagai tambahan kepada tumpuan kepada teknik naratif struktur lain yang penulis gunakan dan cemerlang dalam: Apakah yang mendorong penghasilan teks naratif yang terbilang ini. Selepas membaca novel dan menganalisisnya dengan teliti, pengkaji mendapati bahawa penulis telah menggunakan beberapa siri frekuensi gaya yang membentuk teknik struktur ekspresif. Ia mempunyai kesan yang ketara dalam membentuk teks naratif dalam semua dimensinya. Kata kunci: kekerapan, gaya, teknik naratif, strukturalisme, kisah pelaut